CT-Guided FNAC of Lung Lesions and Cytological Sub-Classification of Bronchogenic Carcinoma of 246 cases at a Tertiary Care Hospital (Journal of Enam Medical College, 2022)
Background: CT-guided fine needle aspiration cytology (FNAC) is a useful tool for evaluating lung nodules or masses. In view of the relative paucity of published studies regionally, this study was undertaken in the Department of Pathology, Enam Medical College & Hospital to see the use of the technique.Materials and Methods: Two forty six CT guided lung FNACs were performed during January 2017 to December 2018 and cytological diagnoses were made. Reported results and relevant data were recorded in the data sheet and then analyzed by standard statistical method.Results: Total number of cases were 246. Adequate samples were obtained in 228 (92.68%) cases, among the adequate samples 135 (59.41%) were malignant, and 93 (40.49%) were benign or nonmalignant lesions. Among the benign lesions, lung abscess (36;38.70%) was the most common followed by pulmonary TB (27;29.03%). Adenocarcinoma (54;40%) was the most common type of bronchogenic carcinoma followed by squamous cell carcinoma (51;37.78%), small cell carcinoma (21;15.56%), NHL (6;4.44%) and large cell undifferentiated carcinoma (3;2.22%). In male persons, squamous cell carcinoma (42.85%) was the most common type of bronchogenic carcinoma, followed by adenocarcinoma (34.29%). In female, adenocarcinoma was the most common type (18;60%) of bronchogenic carcinoma, followed by squamous cell carcinoma (6;20%).Conclusion: FNAC is a safe method for the evaluation of lung nodules and it enables sub-classification of bronchogenic carcinoma in the vast majority of cases. It is also useful for the diagnosis of tuberculous pulmonary nodules.J Enam Med Col 2020; 10(3): 169-173